Love for sale : representing prostitution in imperial Russia - Lucey, Colleen (NIU series in Slavic, East European, and Eurasian studies., 2021)
"During the nineteenth century, Russian writers and artists explored the sex worker's trade, creating iconic works of literature and fine art. This book examines how such representations chart growing concerns about the challenge such sexually transgressive women posed to the social order"